Hypoxia Alters Epigenetic and N-Glycosylation Profiles of Ovarian and Breast Cancer Cell Lines in-vitro - Greville, Gordon; Llop, Esther; Huang, Chengnan; Creagh-Flynn, Jack; Pfister, Stephanie; O'Flaherty, Roisin; Madden, Stephen F.; Peracaula, Rosa; Rudd, Pauline M.; McCann, Amanda; Saldova, Radka (Frontiers in Oncology, 2020)
Background: Glycosylation is one of the most fundamental post-translational modifications. Importantly, glycosylation is altered in many cancers. These alterations have been proven to impact on tumour progression and to promote tumour cell survival. From the literature, it is known that there is a clear link between chemoresistance and hypoxia, hypoxia and epigenetics and more recently glycosylation and epigenetics. Methods and Results: Our objective was to investigate these differential parameters, in an in vitro model of ovarian and breast cancer. Ovarian (A2780, A2780cis, PEO1, PEO4) and triple negative breast cancer (TNBC) (MDA-MB-231 and MDA-MB-436) cells were exposed to differential hypoxic conditions (0.5-2% O2) and compared to normoxia (21% O2). Results demonstrated that in hypoxic conditions some significant changes in glycosylation on the secreted N-glycans from the ovarian and breast cancer cell lines were observed. These included, alterations in oligomannosylated, bisected glycans, glycans with polylactosamine extensions, in branching, galactosylation and sialylation in all cell lines except for PEO1. In general, hypoxia exposed ovarian and TNBC cells also displayed increased epithelial to mesenchymal transition (EMT) and migration, with a greater effect seen in the 0.5% hypoxia exposed samples compared to 1% and 2% hypoxia (p≤ 0.05). SiRNA transient knock down of GATA2/3 transcription factors resulted in a decrease in the expression of glycosyltransferases ST3GAL4 and MGAT5, which are responsible for sialylation and branching respectively. Conclusions: These glycan changes are known to be integral to cancer cell survival and metastases, suggesting a possible mechanism of action, linking GATA2 and 3, and invasiveness of both ovarian and TNBC cells in vitro.